EEG CHARACTERISTICS OF DIFFERENT TYPES OF FOCAL EPILEPSY IN ADULT PATIENTS - Primatov Shaxbozbek Shuxrat o‘g‘li (Web of Journals Publishing, 2023)
The article investigated and analyzed EEG characteristics of different types of focal epilepsy in adult patients by the author.
Keywords: diagnosis, epilepsy, frontal, temporal, parietal, occipital, clinic, treatment.